2018
DOI: 10.3389/fbuil.2018.00038
|View full text |Cite
|
Sign up to set email alerts
|

Torsional Response Induced by Lateral Displacement and Inertial Force

Abstract: Eccentric distribution of stiffness, damping, and mass of a structure, and spatially non-uniform ground motion input to a long or large base mat of a structure are well-known causes of torsional response. We have discovered that the torque generated by horizontal displacement and perpendicular inertial force, which we call the Q-∆ effect, can be a cause of torsional response. We formulated the equation of motion of a single finite-size mass-linear elastic shear and torsion spring model and clarified the resona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…20,21 In addition, the authors found that torsional vibration occurs in bisymmetric buildings owing to horizontal displacements; this is called the "Q-Δ effect." 22,23 In particular, torsional resonance occurs when the torsional natural circular frequency becomes the sum or difference of the two translational natural circular frequencies, and the torsional response increases. This resonance is termed "Q-Δ resonance" and is categorized as autoparametric resonance.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 In addition, the authors found that torsional vibration occurs in bisymmetric buildings owing to horizontal displacements; this is called the "Q-Δ effect." 22,23 In particular, torsional resonance occurs when the torsional natural circular frequency becomes the sum or difference of the two translational natural circular frequencies, and the torsional response increases. This resonance is termed "Q-Δ resonance" and is categorized as autoparametric resonance.…”
Section: Introductionmentioning
confidence: 99%
“…The method to derive the resonance condition is based on the existing literature. [ 12 ] An elastic Euler beam is considered. The restoring force of the column is considered up to the second‐order term that is related to the Q–Δ resonance, which takes into account the geometric nonlinearity.…”
Section: Equations Of Motionmentioning
confidence: 99%
“…Model 0 is the same model that was used in Kohiyama and Yokoyama. [ 12 ] It assumed that the column was modeled as a linear spring, and we used a coefficient of 1/2 for a torque term due to the bending–torsion interaction in consideration of the distribution of the torsional moment, as follows. mtruex¨+cxtrueẋ+kxx=mx¨0, mtruey¨+cytrueẏ+kyy=my¨0, Itrueθ¨+cθtrueθ̇+kθθ=12()cxtrueẋycytrueẏx12()kxkyitalicxy, …”
Section: Shaking Table Test With Double Sine Wave Inputmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the structural system of modern high‐rise buildings is often irregular with considerable eccentricities between the mass and stiffness centers . Even for the buildings with a symmetric plan in design, their real structural system may be asymmetric to some degree due to uncertainties in construction and occupancy.…”
Section: Introductionmentioning
confidence: 99%